Dr. Ali Duman — Deep Plane Facelift - Duman, Ali (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ali Duman, Kazakhstan. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003259; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; kazakhstan